2015
DOI: 10.1007/978-3-319-19773-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Holistic Evaluation of Scientific Essays

Abstract: Abstract. In the US in particular, there is an increasing emphasis on the importance of science in education. To better understand a scientific topic, students need to compile information from multiple sources and determine the principal causal factors involved. We describe an approach for automatically inferring the quality and completeness of causal reasoning in essays on two separate scientific topics using a novel, twophase machine learning approach for detecting causal relations. For each core essay conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In this review, a few studies were identified, aiming to detect connections between key concepts or aim to group students' responses according to semantic similarities rather than lexical similarities. Although designed for science explanatory essay scoring, the structured learning approach using Recurrent Neural Networks (RNN) at the sentence and whole essay level is a promising future research area [29], [28], [59]. Other neural network models based on variations of RNN like LSTM [1], RNN with a co-attention module [65], or even convolution neural network [9] have been successfully implemented for automated essay scoring.…”
Section: Deep Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, a few studies were identified, aiming to detect connections between key concepts or aim to group students' responses according to semantic similarities rather than lexical similarities. Although designed for science explanatory essay scoring, the structured learning approach using Recurrent Neural Networks (RNN) at the sentence and whole essay level is a promising future research area [29], [28], [59]. Other neural network models based on variations of RNN like LSTM [1], RNN with a co-attention module [65], or even convolution neural network [9] have been successfully implemented for automated essay scoring.…”
Section: Deep Learning Approachesmentioning
confidence: 99%
“…However, LSA and other similar approaches such as coherence index (Coh-Metrix, [48]) analysis are made at phrase or sentence level. Therefore, the authors [59] proposed a machine learning approach that combines the NLP system developed by Hughes [28] with LSA indices on similarity Coh-Metrix indices on coherence.…”
Section: Student Problem-solving Performancementioning
confidence: 99%
“…The UNKNOWN token occurs frequently enough that it does not carry strong semantic content for the system, similar to words like "a" or "the". Then we applied our machine learning approach with a 7-word sliding window across the text to identify concepts within that window (Hughes et al, 2015). The fixed-size sliding window approach allows us to avoid the difficulties for machine learning from variable-length input, but the size of the window ensures that the words of a concept will almost always fall entirely within one of the windows (Hughes et al, 2015).…”
Section: Concept Detectionmentioning
confidence: 99%
“…Then we applied our machine learning approach with a 7-word sliding window across the text to identify concepts within that window (Hughes et al, 2015). The fixed-size sliding window approach allows us to avoid the difficulties for machine learning from variable-length input, but the size of the window ensures that the words of a concept will almost always fall entirely within one of the windows (Hughes et al, 2015). For each of the concept codes (the nodes in Figure 2), we trained a logistic regression classifier in which the features were the words and the bigrams within the window, as well as their relative positions within the window.…”
Section: Concept Detectionmentioning
confidence: 99%
“…These subtasks related to comprehending evidence in relation to ideas, evaluating ideas in relation to evidence, and producing explanations based on evidence are complex and difficult. Most students have trouble with explanation and argumentation across all subject areas [6][7][8][9], but particularly with argumentation and explanation in science [10][11][12][13][14]. For instance, student explanations often focus on a single major cause to explain the scientific phenomena in question (i.e., lack completeness), while ignoring enabling and mediating factors (i.e., lack coherence) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%